Communicating The Amil Zakat National Agency (BAZNAS) and Its Authority Based on the Zakat Management Act (23/2011) in Indonesi - Kholil, Kholil; Amrullah, Andi; Faiz, Fahrudin (Advances in Social Sciences Research Journal, 2022)
This research aimed to see how BAZNAS communicates its authority based on Law 23/2011 to its stakeholders. Zakat management in Indonesia is being regulated by the Law Number 23 of 2011 which replaced Law Number 38 of 1999. The change of regulation was expected to push Zakat collection higher as its great potential, but until 2019 there was no significant change in the amount of Zakat collection. We see the problem in the authority changes that have not working optimally. Thus, this research can help BAZNAS to map out the problems related to the implementation of Law 23/2011. The research used a qualitative approach by conducting in-depth interviews, library and documentation studies. Eleven expert informants were chosen for their connection and understanding of BAZNAS. The results showed that the BAZNAS authority was accepted by all stakeholders even though it did not take place as the prerequisite for the acceptance of Barnard’s authority. The changes in authority had been understood by the leaders but only halfway understood by the employees. The changes in the authority were following the vision and mission of BAZNAS. However, they were still not in line with the expectations of many parties. Finally, the changes in the BAZNAS authority were still not fully implemented by BAZNAS stakeholders. The regulatory changes could not be fully implemented yet due to differences in the interpretation of legal authority between each level of BAZNAS.